Feasibility of an Online Langerian Mindfulness Program for Stroke Survivors and Caregivers. (July 2022) - Demers, Marika; Pagnini, Francesco; Phillips, Deborah; Chang, Brianna; Winstein, Carolee; Langer, Ellen
Mindfulness is promising for individuals with neurological disorders and their caregivers to improve psychological well-being. The potential application of a Langerian mindfulness intervention, focused on attention to variability, however, is still unknown. The objective of the study was to determine the feasibility (usability, satisfaction, and potential effectiveness on psychological well-being) of an online mindfulness intervention for stroke survivors and caregivers. Using mixed methods, 11 stroke survivors and three caregivers participated in a 3-week, online, Langerian mindfulness intervention. A semi-structured interview assessed the intervention's usability and gathered feedback. Self-reported measures about psychological well-being were documented remotely 3 times (preintervention, postintervention, and 1-month follow-up). Qualitatively, participants were highly satisfied with the intervention and reported subjective benefits, but the usability of the online platform was poor. None of the self-reported measures changed over time. This study provided evidence of feasibility of an online Langerian mindfulness intervention in a new population: stroke survivors and caregivers.